Les and Rans Analysis of the End-Wall Flow in a Linear Lpt Cascade, Part I: Flow and Secondary Vorticity Fields Under Varying Inlet Condition - Pichler, Richard; Zhao, Yaomin; Sandberg, Richard; Michelassi, Vittorio; Pacciani, Roberto; Marconcini, Michele; Arnone, Andrea (Journal of Turbomachinery, 2019)
In low-pressure-turbines (LPT) around 60-70% of losses are generated away from end-walls, while the remaining 30-40% is controlled by the interaction of the blade profile with the endwall boundary layer. Experimental and numerical studies have shown how the strength and penetration of the secondary flow depends on the characteristics of the incoming end-wall boundary layer. This paper discusses the endwall flow characteristics of the T106 LPT profile at Re=120K and M=0.59 by benchmarking with experiments and investigating the impact of the incoming boundary layer state. The simulations are carried out with proven Reynolds-averaged Navier–Stokes (RANS) and large-eddy simulation (LES) solvers to determine if Reynolds Averaged models can capture the relevant flow details with enough accuracy to drive the design of this flow region. Part I of the paper focuses on the critical grid needs to ensure accurate LES, and on the analysis of the overall time averaged flow field and comparison between RANS, LES, and measurements when available. In particular, the growth of secondary flow features, the trace and strength of the secondary vortex system, its impact on the blade load variation along the span and end-wall flow visualizations are analyzed. The ability of LES and RANS to accurately predict the secondary flows is discussed together with the implications this has on design.
Keywords: boundary layer development; cfd; computational fl uid dynamics; computational fluid dynamics (CFD); dynamics and heat transfer; fl uid; fluid dynamics and heat transfer phenomena in comp; phenomena in compressor and; turbine components of gas